New Zealand exports of education services - New Zealand Trade; Economic Analysis Division of the Ministry of Foreign Affairs; Trade (New Zealand Institute of Economic Research (NZIER), 2000)
The education export industry is an important and growing sector of the economy. This study examines the foreign exchange contribution of international students (the largest component of this sector) to the New Zealand economy and provides a base from which work can be extended to assess the nature of this key service industry.
Keywords: 330; Studium; Ausländer; Studienfinanzierung; Lebenshaltungskosten; Neuseeland